Analisis Model Pembelajaran Think Pair Share (TPS) Terhadap Keterampilan Berfikir Krtitis Pada Pembelajaran PPKn Siswa Sekolah Dasar - Lofha, Prichilia Hasintha; Rondli, Wawan Shokib (Peneliti.net, 2025)
Civics learning in elementary schools is often less effective in developing students' critical thinking skills. The Think Pair Share (TPS) learning model is considered as an alternative that can increase students' active participation and critical thinking abilities. The aim of this research is to analyze the effect of implementing the Think Pair Share (TPS) learning model on elementary school students' critical thinking skills in Civics learning. In this study, the approach taken is a qualitative method using a case study design to explore the phenomenon in depth and detail. This is done to characterize students' character traits in critical thinking training. The research results show that the application of the Think Pair Share (TPS) learning model has a positive impact on primary school students' critical thinking skills in Civics learning. Students become more active in the learning process, especially when discussing with partners and sharing ideas with the class and there is an increase in the ability to analyze information and ask critical questions. There is an increase in students' ability to evaluate arguments and make judgments based on evidence. This case study concludes that the Think Pair Share (TPS) learning model is effective in improving analysis, evaluation and problem solving skills and abilities better than conventional methods.